HUBUNGAN MUTU PELAYANAN ANC DENGAN TINGKAT KEPUASAN IBU HAMIL DI PUSKESMAS SEBERANG PADANG KOTA PADANG - Rahmawati, Lisa; Ningsih, Mahdalena Prihatin; Yusrialmi, Sherli Prima (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
The satisfaction of pregnant mother have a relation with quality of antenatal care service. The patients who feel satisfied with the quality of antenatal service, they will come back to get the service again and recommend the service to others. Of the 22 public health care in thePadang, the health care with the lowest ANC obtained by PHC Seberang Padang is equal (67.66%) with the targets should be 95%. The purpose of the study to determine the relationship between Quality of ANC Service with the Satisfaction Level At Pregnant Mother in Seberang Padang Primary Health Care, Padang district. The type of study is analytic survey with cross sectional design. The place of study in PHC Seberang Padang in 2017. With a population of 367 peoples, and a sample of 40 peoples are taken by accidental sampling. The study was conducted on using of computerized systems and analyzed by univariate and bivariate. The results of Chic-square test, there is a relationship between the dimensions of quality of responsiveness (p value: 0.002), dimensions of quality of reliability (p value: 0.000), dimensions of quality of assurance (p value: 0.000), dimensions of quality of empathy (p value: 0,000), quality dimension tangibles (p value: 0.000), and quality of ANC service with the satisfaction level at pregnant mother in PHC of Seberang Padang (p value: 0.000). The conclusion is there is a relationship between the Quality of ANC Service with the Satisfaction Level at Pregnant Mother in Primary Health Care Seberang Padang. Suggestions to PHC of Seberang Kota Padang is in order to improve all dimensions ofÂ  quality of ANC causing pregnant mother satisfaction. Keywords: Quality, Satisfaction